KINERJA KOMISI PIMILIHAN UMUM KOTA PEKANBARU DALAM PENGADAAN DAN PENDISTRIBUSIAN LOGISTIK PEMILIHAN UMUM 2019 - Freddy Markoes; Hasanuddin ' (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
The General Election Commission. On 17 April 2019, for the first time, Indonesia carried out simultaneous voting for the legislative and executive, at the district/city, provincial and central levels. This is expected to be able to reduce the budget for holding elections, and voters can be wiser in voting in line with the legislative and executive. Simultaneous elections on April 17 2019 there were still many problems in the implementation process, one of the obstacles was the availability of ballot papers, this problem can be traced starting from the stages of procurement and distribution of election logistics. The purpose of this research is to find out the performance of the Pekanbaru City KPU in holding simultaneous elections on April 17 2019, especially in terms of procuring and distributing ballot papers. This study uses a qualitative approach with descriptive methods, in terms of data collection, the authors use interview techniques, browse related documents and documentation. The results of this study are that the implementation of simultaneous elections carried out by the KPU is in accordance with the schedule and stages set, the shortage of ballots at the time of the election is due to changes in the DPTHP 3 belonging to the Pekanbaru City KPU, where the RI KPU is no longer able to accommodate ballots due to time constraints. because of that the accommodation for the Pekanbaru City KPU was based on DPHTP 2 while the Pekanbaru City KPU's DPTHP 3 was annulled by the RI KPU. Keywords: implementation, simultaneous elections, procurement, distribution